Increased Spinal Cord Stimulator Use and Continued Opioid Treatment Among Injured Workers: A Regional Pilot Study. Issue 8 (August 2020) - Leung, Nina; Tsourmas, Nicholas F.; Yuspeh, Larry; Kalia, Nimisha; Lavin, Robert A.; Tao, Xuguang (Grant); Bernacki, Edward J.
Abstract : Objective: To determine the rate, characteristics, and costs of Spinal Cord Stimulator (SCS) placements among claimants at a Texas-based workers' compensation carrier. Methods: Indemnity claims occurring between January 1, 2008 and December 31, 2018 were assessed longitudinally. Results: While there was annual variability in rates of SCS placement, the rate of SCS placement increased from 0.21 to 1.56 per 1000 serviced claims. The average total paid claim cost of a trial and permanent placement was 141, 288 and 197, 813, respectively. Chronic opioid use (more than 3 months) following trial (73.0%) and permanent placement (63.8%) occurred frequently. Time between injury and trial placement decreased (2008 to 2010 = 3.1 years vs 2015 to 2018 = 2.5 years, P < 0.0001) over the study period. Conclusions: The rate of SCS placements significantly increased and duration between injury to placement decreased over time. Claimants undergoing SCS placement frequently continued to use opioids, indicating limited success in pain modulation. Abstract : Supplemental Digital Content is available in the text